PENGARUH MIKROORGANISME, BAHAN BAKU, DAN WAKTU INKUBASI PADA KARAKTER NATA: REVIEW - Putri, Sherly Novia Yuana; Syaharani, Wahyu Fajri; Utami, Cindy Virgiani Budi; Safitri, Dyah Retno; Arum, Zahra Nur; Prihastari, Zulfa Shafira; Sari, Anjar Ruspita (Jurnal Teknologi Hasil Pertanian, 2021)
Nata is an organic food product that has a high fiber content. Nata is a fermented produce by Acetobacter xylinum. There is very limited review article that discussed the making process of nata using different starter, raw material, and the length of incubation time in once. So that, this review discusses the comparison of various parameters that affect the fermentation process of nata. This review aims to discuss the effect of using several types of microorganisms, different raw materials, and different fermentation time on nata production. Factors that influence the success of nata fermentation process include fermentation time, the addition of ingredients (sugar, vinegar, and urea), the use of hollow caps, avoiding products from shocks, and the use of sterile equipment. The bacteria that can be used for making nata include Acetobacter xylinum and Acetobacter sp. Several raw materials can be used to make nata, such as coconut water, seaweed, banana peels, tofu water, cassava, and jackfruit straw. The best raw material to make nata from color parameters is seaweed, aroma parameter is jackfruit straw, and taste parameter is cassava. Based on chemical and physical tests, the best raw material for moisture content parameters is seaweed, fiber content parameter is cassava, thickness parameter is banana peel, and yield parameter is coconut water followed by cassava. The length of fermentation affects the thickness and weight of nata, chewier texture of nata, and the darker color of nata. The best thickness of nata produced on the 14th day of fermentation was 1.7 cm. The best overall weight of nata on produced the 10th day of fermentation was 600 g/L. The texture of nata was the chewiest in the fermentation time of 14 days with the value was 72.33 g/5mm. The lowest degree of nata whiteness produced on the 14th day of fermentation with the value was 72.307%.